2012
DOI: 10.4161/viru.21823
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells, regulatory T cells and the pathogenesis of chronic hepatitis C

Abstract: Hepatitis C virus (HCV) is a small, enveloped RNA virus and a major cause of chronic liver disease. Resolution of primary HCV infections depends upon the vigorous responses of CD4+ and CD8+ T cells to multiple viral epitopes. Although such broad-based responses are readily detected early during the course of infection regardless of clinical outcome, they are not maintained in individuals who develop chronic disease. Ostensibly, a variety of factors contribute to the diminished T cell responses observed in chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 137 publications
1
35
0
Order By: Relevance
“…Lee et al (2001) demonstrated that HCV core protein, which is either expressed within macrophage cells or exogenously added to them, is capable of suppressing IL-12 production by activated APCs. In addition, HCV core protein was shown to exert an inhibitory effect on the stimulatory capacity of macrophages in mixed lymphocyte reaction (Losikoff et al, 2012). Taken together, these results suggested that HCV core protein could play significant roles in suppressing the effective HCV-specific Th1 immunity through inhibition of IL-12 secretion and inhibition of macrophage functions, which may contribute to persistent HCV infection.…”
Section: Discussionmentioning
confidence: 84%
“…Lee et al (2001) demonstrated that HCV core protein, which is either expressed within macrophage cells or exogenously added to them, is capable of suppressing IL-12 production by activated APCs. In addition, HCV core protein was shown to exert an inhibitory effect on the stimulatory capacity of macrophages in mixed lymphocyte reaction (Losikoff et al, 2012). Taken together, these results suggested that HCV core protein could play significant roles in suppressing the effective HCV-specific Th1 immunity through inhibition of IL-12 secretion and inhibition of macrophage functions, which may contribute to persistent HCV infection.…”
Section: Discussionmentioning
confidence: 84%
“…Accumulating evidence indicates that patients with chronic viral hepatitis display an increased number of Treg cells in peripheral blood or liver; however, the increment of Treg cells in CHC and their role in liver damage development is still a matter of debate [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Tregs expand during HCV infection in humans and this has been suggested to be involved in the establishment of a persistent infection [7, 62, 63]. CD4 + CD25 + Tregs isolated from HCV-infected patients inhibit antiviral CD8 + T cell responses while depletion of CD4 + Tregs enhances proliferation of remaining T cells [64, 65].…”
Section: Introductionmentioning
confidence: 99%